2013
DOI: 10.1016/j.ijsu.2013.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of perforated peptic ulcer: Patch versus simple closure

Abstract: Laparoscopic simple repair of PPU is a safe procedure compared with the traditional patch omentoplasty in presence of certain selection criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
2
24
0
1
Order By: Relevance
“…Comparison of the operating time in the 4.0-and 5.0-12mm groups reported that the simple closure took less time than omentopexy for perforations smaller than 12 mm. Abd Ellatif and colleagues [55] enrolled 179 consecutive patients with PPU who were treated by laparoscopic repair; 108 patients with the omental patch technique and 71 with laparoscopic simple repair. Operative time was significantly shorter in the non-patch group and no patient was converted to laparotomy.…”
Section: Surgerymentioning
confidence: 99%
“…Comparison of the operating time in the 4.0-and 5.0-12mm groups reported that the simple closure took less time than omentopexy for perforations smaller than 12 mm. Abd Ellatif and colleagues [55] enrolled 179 consecutive patients with PPU who were treated by laparoscopic repair; 108 patients with the omental patch technique and 71 with laparoscopic simple repair. Operative time was significantly shorter in the non-patch group and no patient was converted to laparotomy.…”
Section: Surgerymentioning
confidence: 99%
“…Sutureless techniques have also been developed using a gelatin sponge and fibrin glue to seal off the perforation [55]. There seem to be no significant differences in terms of postoperative morbidity and mortality rates when comparing primary closure, omentopexy or tegmentation (without closure) [55][56][57]. Surgical repair can be performed either with conventional open surgery or with laparoscopy.…”
Section: Simple Surgical Repairmentioning
confidence: 99%
“…In the present study, the mean operation time was 66.7±19.6 minutes, which is comparable to previously reported results for laparoscopic simple closure techniques without omental patch. 16,17 Open conversion rates have been reported to range from 0% to 28.5%, and the most common causes of conversion are large perforation size (usually >10 mm), inadequate ulcer location, and difficult suturing due to friable ulcer edge. 13 In the present study, large (>10 mm) duodenal wall defects as visualized on perioperative CT scan were treated by open surgery and excluded from the study, so it is impossible to determine whether larger duodenal ulcer perforations can be safely managed us-ing our surgical technique.…”
Section: (3~8)mentioning
confidence: 99%